Can children ask parents to seek inpatient mental Healthcare? –An answer from Zhu Xi - Leong, Jia Qi (Nanyang Technological University, 2024)
As this paper is on elder care, it will dive deeper into the context of eldercare in East Asia. Then, mental healthcare ethics, specifically medical principalism will be described in detail. This paper will argue that an adult child is morally allowed to seek mental healthcare treatment for their parent in East Asia. This is because once the adult child applies Zhu Xi’s ethics to medical principalism, they would be able to ensure that the act adheres to the moral requirements that make an act moral. The paper will also argue that the adult child is able to circumvent the expected caregiving norms across Asia and allows the adult to be morally allowed to ask their parent to seek mental healthcare help.